The Assessment of Psychiatric Disorders in Intellectual Disability: The State of the Art - Marco O. Bertelli, Marco O. Bertelli; Michele Rossi, Michele Rossi; Daniela Scuticchio, Daniela Scuticchio; Annamaria Bianco, Annamaria Bianco; Luana Salerno, Luana Salerno (Journal of Intellectual Disability - Diagnosis and Treatment, 2015)
Intellectual Disability (ID) represents a meta-syndromic group of several different conditions, each one with specific cognitive and communication features. This constitutes one the main reason for which the diagnosis of psychiatric disorders in adults with ID is challenging. The aim of this paper is to provide a comprehensive and updated state of art on the assessment of psychiatric disorders in people with ID. In order to accomplish this goal, authors performed a systematic literature mapping trying to answer to the following questions: what are the issues in the psychiatric diagnostic process for adults with ID? What methods and procedures have been used for psychiatric assessment in ID? To date, is it possible to identify the most effective diagnostic procedures? Results indicated that the main critical issues in the psychiatric diagnostic process were the following: the identification of psychiatric symptoms, the behavioural equivalents, the diagnostic criteria, the setting, the source of information, the screening and diagnostic instruments. An increasing interest in screening instruments for providing appropriate diagnosis for people with ID has been noted in the recent years. For this reason, available assessment tools have been briefly indicated, with their strengths and weaknesses. Although the recent advances, more research is needed in order to increase diagnostic accuracy in this heterogeneous group of patients.